2017
DOI: 10.1111/1471-0307.12477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cactus pear (Opuntia ficus‐indica (L.) Miller) on the antioxidant capacity of donkey milk

Abstract: The cladodes of Opuntia ficus‐indica (L.) Miller were fed to lactating donkeys as an alternative food, in order to evaluate effects on the chemical composition and antioxidant activity of their milk. Lactating donkeys were divided into two groups: standard feeding and alternative feeding. With regard to chemical composition, no differences were observed. Total antioxidant capacity was constant in the standard feeding group, while it increased in the alternative feeding group: the radical scavenging activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In particular, lipid supplementation has variable effects that depend on the added lipids and their interaction with types of forage and concentrate in the diet (Antongiovanni et al, 2003;Chilliard et al, 2003). Moreover, several studies (Renna et al, 2012;Cosentino et al, 2018;Valentini et al, 2018) show a strong relationship between the diet of lactating animals and the aromatic quality of milk and dairy products. Several oilseeds, such as sunflower and linseed, have been widely used in diets for small ruminants because they are rich in PUFA, which positively influence the FA profile of animal products, and thus have beneficial effects for human health (Giannico et al, 2009;Colonna et al, 2011;Facciolongo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, lipid supplementation has variable effects that depend on the added lipids and their interaction with types of forage and concentrate in the diet (Antongiovanni et al, 2003;Chilliard et al, 2003). Moreover, several studies (Renna et al, 2012;Cosentino et al, 2018;Valentini et al, 2018) show a strong relationship between the diet of lactating animals and the aromatic quality of milk and dairy products. Several oilseeds, such as sunflower and linseed, have been widely used in diets for small ruminants because they are rich in PUFA, which positively influence the FA profile of animal products, and thus have beneficial effects for human health (Giannico et al, 2009;Colonna et al, 2011;Facciolongo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ibrahim et al studied the effects of OG and/or bifidobacterium producing exopolysaccharide on the physical properties, fermentation time, and sensory evaluation of low-fat yogurt, and the result showed that the OG and bifidobacterium produced exopolysaccharide in low-fat yogurt, improved the physical and sensory properties of yogurt, and enhanced probiotics activity [11]. Valentini et al found that the cactus pear (L.) Miller), as an alternative substitute feeding, increased the antioxidant capacity of donkey milk [12]. In short, OG has good solubility, high viscosity, thickening, and other processing characteristics, which improve the texture and structure of yogurt, and it also has prebiotic properties.…”
Section: Whcmentioning
confidence: 99%